Ethno-STEAM as a culturally responsive framework: Examining collaborative skills through Kawung batik design - Astuti, Dwi; Retnawati, Heri; Prahmana, Rully Charitas Indra (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2026)
Twenty-first-century education necessitates that students cultivate collaborative competencies in tandem with cognitive abilities. However, structured pedagogical models for developing and assessing collaboration remain limited, particularly those grounded in culturally responsive frameworks. This study examines the implementation of the Ethno-STEAM learning model, which integrates ethnomathematical principles with interdisciplinary STEAM education through the LOCAL syntax—Link with Culture, Observe and Organize, Connect with STEAM, Act through Creation, and Learn and Reflect. The model explicitly aligns each instructional stage with specific indicators of collaboration: active engagement, social interaction, decision-making, and evaluative reflection. Employing a mixed-methods design, the study involved 84 eighth-grade students from three junior high schools in Yogyakarta, Indonesia. Data were collected through self-assessment questionnaires, peer evaluations, classroom observations, and structured interviews. Quantitative data were analyzed using descriptive statistics and paired-samples t-tests to compare self- and peer-assessment scores, while qualitative data underwent thematic analysis to elucidate students’ reflections on collaboration at each stage of the LOCAL model. The quantitative results indicated moderate to high levels of collaboration, with the highest mean score in social interaction (M=3.27) and the lowest in decision-making (M=3.04). A statistically significant difference was found between self- and peer-assessment scores, t(83)=2.204, p=.030, d=.240, suggesting that students exhibited positive self-awareness while also benefiting from multiple evaluative perspectives. Thematic findings revealed that engagement with cultural contexts enhanced active participation, and that gender-based communication tendencies affected the quality of social interaction. Finally, the LOCAL model effectively scaffolds the development of students’ collaborative competencies in culturally meaningful ways. It provides educators with a systematic, pedagogically grounded framework that unites ethnomathematical values with the interdisciplinary goals of 21st-century STEAM education.